2012
DOI: 10.5146/tjpath.2012.01094
|View full text |Cite
|
Sign up to set email alerts
|

Cd117 and cd34 staining patterns in childhood benign mammary lesions

Abstract: Objective: CD117 and CD34 are markers that have both been implied in cancer progression in adult breast lesions. This study was conducted in order to create a retrospective documentation and to analyze the expression patterns of these markers on childhood benign lesions along with a comparison with adult breast lesions' staining patterns. Material and Method:Nine fibroadenomas, 2 tubular adenomas, 1 mammary hamartoma, 2 gynecomastias, 1 benign phyllodes tumor were retrieved from pathology archives of two refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Paraffin blocks from 47 individual patients, four fresh specimens of malignant PT and their xenografted tumors, were examined by immunohistochemical staining for the following markers: CD44 (HCAM), CD29 (integrin β-1), CD106 (VCAM-1), CD166 (ALCAM), CD105 (Endoglin), CD90 (Thy-1) [17-20], GD2 (ganglioside) [11], CD117(c-kit receptor) [21], ALDH1 [15], embryonic stem cell marker Oct-4 (Octamer-4 in abbreviation), CD34 [22], CD10, p53, p63, Ki-67, Bcl-2 [23] and vimentin [24]. Mesenchymal progenitor cell-line HS-5 was chosen as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Paraffin blocks from 47 individual patients, four fresh specimens of malignant PT and their xenografted tumors, were examined by immunohistochemical staining for the following markers: CD44 (HCAM), CD29 (integrin β-1), CD106 (VCAM-1), CD166 (ALCAM), CD105 (Endoglin), CD90 (Thy-1) [17-20], GD2 (ganglioside) [11], CD117(c-kit receptor) [21], ALDH1 [15], embryonic stem cell marker Oct-4 (Octamer-4 in abbreviation), CD34 [22], CD10, p53, p63, Ki-67, Bcl-2 [23] and vimentin [24]. Mesenchymal progenitor cell-line HS-5 was chosen as a control.…”
Section: Resultsmentioning
confidence: 99%
“…A cutoff point was not used here, but rather the association between the immunoreactivity score and tumor types. In a study on breast lesions in adolescents, Kaçar et al 32 reported that, in all 9 evaluated fibroadenomas (6 of which were cellular type), there was diffuse epithelial expression of CD117, being only focal in the epithelium of the benign PTB of the series. Yared et al 33 presented a possible explanation for this finding, where a strong and diffuse expression of CD117 in the epithelium of normal breast tissue was found, which progressively diminished in hyperplastic lesions, fibroadenomas, and papillomas until carcinomas, suggesting a loss of epithelial expression as the neoplastic progression occurs.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of mast cells expresses SCF (Stem cell Factor) which can bind to its receptor C-KIT (also known as CD 117; a type of receptor tyrosine kinase). It has been shown that increased C-KIT expression noted in these spectrum of benign breast neoplasms in varying proportion is a mast cell phenomenon and mast cell derived mediators may play a role in progression to borderline and malignant phyllodes tumours [16][17][18][19].…”
Section: Original Research Article Pathology Update: Tropical Journalmentioning
confidence: 99%